Avaliação do coproduto da castanha-do-Pará como fonte natural e orgânica de metionina em dietas para codornas japonesas na fase de postura. - Oliveira, Thalis José de (2020)
The aim was to develop a model of organic diet with a natural source of methionine, thereby adding value to Japanese quail eggs. First trial: the chemical composition and apparent metabolizable energy (AME) and AME corrected for nitrogen balance (AMEn) of conventional corn (CONVC), organic corn (ORGC), conventional soybean meal (CONVSBM), organic soybean meal (ORGSBM) and organic soybean meal and Brazil nut of coproduct organic (BNCO), were evaluated. The BNCO was evaluated as an energy, protein source and as a substitute for removing synthetic sources of methionine from the laying quail organic diet. The energy values were estimated in a metabolism test carried out in a completely randomized design with 180 Japanese quails, 105 days old, selected by body weight and laying rate. The traditional method of total excreta collection was used, with six treatments, five of which were experimental and a reference diet, each treatment with five repetitions of six birds. Each experimental diet consisted, on the basis of natural matter, for 60% of the reference diet and 40% of the ingredient to be tested. The BNCO had a higher crude protein content (34.40%) than the two types of conventional and organic corn and less than the two types of soybean meal, and the ether extract content (29.37%) higher than the two types of corn and soybean meal. The BNCO's AME and AMEn of, respectively, 3.815 and 3.790kcal / kg were higher than that of the CCONV of 3,353 and 3,295kcal / kg, of the CORG of 3,247 and 3,174 kcal / kg; the CONVSBM of 2,782 and 2,426 kcal / kg and the ORGSBM of 2,937 and 2,519 kcal / kg. However, better coefficients of gross energy metabolization were observed for CCONV (93.68%) and CORG (89.13%), compared to BNCO (75.97%) and CONVSBM (65.13%) and ORGSBM (61.51%). Second trial: the productive responses of 180 quails were evaluated, distributed in a completely randomized design, composed of five treatments, three conventional diets based on corn and conventional soybean meal and supplemented with DL - Met; L - Met and MHA Ca and two organic diets based on corn and organic soybean meal, one without the source of methionine and the other supplemented with organic by-product of the Brazil nut, each treatment with six repetitions of six birds. The quail groups that received diets containing C + SBM CONV + synthetic methionine (DL-Met, L-Met and MHA-Ca) consumed more (p≤0.05) compared to groups fed with organic diets (C + SBM and C + SBM BNCO). The best results of egg production, egg weight and egg mass were observed in the quail groups fed with C + SBM CONV + DL-Met and BNCO that did not differ (p> 0.05). The best results of feed conversions per dozen and per mass of eggs were observed for quails receiving the organic mixture containing BNCO as a source of amino acids. The components of yolk and shell weight were lower in the treatment of organic diet C + SBM without supplementation of sources of methionine and BNCO (p <0.05). The by-product of Brazil nuts is a strategic ingredient for organic cotton farming because it completely replaces synthetic sources of methionine in organic Japanese quail diets.